ANTI-INFLAMMATORY AND ANALGESIC ACTIVITY OF R.A.P. (RADIX ANGELICAE PUBESCENTIS) ETHANOL EXTRACTS - Li, Xiaorong; Wang, Jiangning; Gao, Lei (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this paper was to study the anti-inflammatory and analgesic effects of Radix Angelicae Pubescentis (R.A.P) ethanol extracts. Three classic anti-inflammatory models and two analgesic models were used in this research. In anti-inflammatory tests, all the extracts have a certain inhibition on the acute inflammation induced by xylene, however, 60% ethanol extract significantly inhibited the inflammation in the three models. In analgesic experiment, compared with the blank control group, the comparisons between R.A.P. groups and control group had significant difference (p﹤0.01). The incubation period in mouse writhing test or the tail-curl immersion tests could be extended greatly.